Morphologically Different Pectobacterium brasiliense Bacteriophages PP99 and PP101: Deacetylation of O-Polysaccharide by the Tail Spike Protein of Phage PP99 Accompanies the Infection - Lukianova, Anna A.; Shneider, Mikhail M.; Evseev, Peter V.; Shpirt, Anna M.; Bugaeva, Eugenia N.; Kabanova, Anastasia P.; Obraztsova, Ekaterina A.; Miroshnikov, Kirill K.; Senchenkova, Sofiya N.; Shashkov, Alexander S.; Toschakov, Stepan V.; Knirel, Yuriy A.; et al. (Frontiers in Microbiology, 2020)
Soft rot caused by numerous species of Pectobacterium and Dickeya is a serious threat to the world production of potatoes. The application of bacteriophages to combat bacterial infections in medicine, agriculture, and the food industry requires the selection of comprehensively studied lytic phages and the knowledge of their infection mechanism for more rational composition of therapeutic cocktails. We present the study of two bacteriophages, infective for the Pectobacterium brasiliense strain F152. Podoviridae PP99 is a representative of the genus Zindervirus, and Myoviridae PP101 belongs to the still unclassified genomic group. The structure of O-polysaccharide of F152 was established by sugar analysis and 1D and 2D NMR spectroscopy: → 4)-α-D-Manp6Ac-(1→ 2)-α-D-Manp-(1→ 3)-β-D-Galp-(1→ 3↑1α-l-6dTalpAc0−2 The recombinant tail spike protein of phage PP99, gp55, was shown to deacetylate the side chain talose residue of bacterial O-polysaccharide, thus providing the selective attachment of the phage to the cell surface. Both phages demonstrate lytic behavior, thus being prospective for therapeutic purposes.